Direct and correlated responses to selection in two lines of rabbits selected for feed efficiency under ad libitum and restricted feeding: III. Digestion and excretion of nitrogen and minerals. Issue 3 (1st March 2017) - Gidenne, T.; Fortun-Lamothe, L.; Bannelier, C.; Molette, C.; Gilbert, H.; Chemit, M. L.; Segura, M.; Benitez, F.; Richard, F.; Garreau, H.; Drouilhet, L.
Abstract: Two rabbit lines have been created to result in better feed efficiency: the ConsoResidual line was selected for a lower residual feed intake under ad libitum feeding, and the ADGrestrict line was selected for higher ADG under restricted feeding (−20% of ad libitum). The present study aimed to analyze the digestion and excretion of N and minerals from 29 to 63 d of age of these 2 lines compared with an unselected control line (G0) under 2 feeding levels (ad libitum or restricted). The ADGrestrict line had greater digestibility compared with G0 (+1.3% for OM and N; P < 0.05), and the ConsoResidual line had intermediate values. There was no genetic line effect on the digestibility of N and P and on minerals concentrations (P, Zn, and Cu) in the feces and in the urine. The N balance was improved for the 2 selected lines (+5%; P < 0.05), leading to a reduced N output through the feces (0.06 g/d compared with G0; P < 0.001) and the urine (−0.07 g/d; P < 0.05) and to an improved N retention ratio (+3% compared with G0). Over the whole fattening period (d 29–63), significant differences were observed among lines only when fed ad libitum, with 13% greater DM fecal output and 5% greater N fecal output for G0. The N excretion in urine was 2 g less in the 2 selected lines, leading to a reduction of total N release of 4.4 g (compared with G0). The P excretion in feces (12 g) or urine (0.1 g) did not differ among the 3 lines. Over the whole fattening period and for ad libitum–fed rabbits, the 5% improvement in feed efficiency ( P < 0.01) for the 2 selected lines corresponded to 400 g less feed intake (−8%) and to 20 g less N intake. The fecal excretion of the ADGrestrict and ConsoResidual lines were reduced by 200 g DM ( P < 0.01), corresponding to 417 g fresh matter and 5 g of N. The excretion in minerals (P, Zn, and Cu) was not affected by the line. The feeding level strongly reduced the fecal and urine outputs (−50 and −60%, respectively; P < 0.001). Higher digestibility coefficients ( P < 0.001) were found in restricted-fed rabbits for OM (+6%), N (+8%), and P (+11%). The N balance was substantially improved by the restriction, with 40% less total (feces + urine) N excretion ( P < 0.001). The P balance was improved by the restriction (0.469 vs. 0.360). Over the fattening period, the P fecal output was 37% less (−6 g) with 24% less feed intake and the Zn and Cu outputs were reduced by 27 (−130 mg) and 29% (−30 mg), respectively.